2015
DOI: 10.1016/j.yhbeh.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine dyscrasia that accompanies menopause and andropause induces aberrant cell cycle signaling that triggers re-entry of post-mitotic neurons into the cell cycle, neurodysfunction, neurodegeneration and cognitive disease

Abstract: Sex hormones are the physiological factors that regulate neurogenesis during embryogenesis and continuing through adulthood. These hormones support the formation of brain structures such as dendritic spines, axons and synapses required for the capture of information (memories). Intriguingly, a recent animal study has demonstrated that induction of neurogenesis results in the loss of previously encoded memories in animals (e.g. infantile amnesia). In this connection, much evidence now indicates that Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 368 publications
(433 reference statements)
0
15
0
Order By: Relevance
“…Previous studies support the idea that multiple factors involved in menopause-induced brain damage, for example, synapse loss, neuronal loss, blood-brain barrier disruptions, white matter degeneration, and so on (Atwood and Bowen 2015;Kantarci et al 2018). Thus, considerable changes after menopause must be more rigorously considered.…”
mentioning
confidence: 92%
“…Previous studies support the idea that multiple factors involved in menopause-induced brain damage, for example, synapse loss, neuronal loss, blood-brain barrier disruptions, white matter degeneration, and so on (Atwood and Bowen 2015;Kantarci et al 2018). Thus, considerable changes after menopause must be more rigorously considered.…”
mentioning
confidence: 92%
“…Hypogonadotropic hypogonadism as a result of acute (≤ 80% of cases) and/or chronic (~40% of cases) TBI could therefore greatly compromise neuroregeneration and recovery from a TBI. In this respect, it is well recognized that the endocrine dyscrasia that results from menopause and during andropause has a negative impact on cognitive function, and that hormone supplementation with physiological human sex steroids can halt or reverse the cognitive decline associated with aging [ 16 , 17 ]. These data indicate the need to develop strategies to rebalance the HPG hormones following TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated the efficacy of increasing sex steroids and suppressing gonadotropins in reversing neurodegeneration and cognitive decline in animal models of AD (reviewed in [98, 184]). Preclinical studies in mouse models of AD also have demonstrated that specific inhibitors of the cell cycle, such as the oral administration of the synthetic retinoid X receptor-selective retinoid bexarotene, stimulates the rapid reversal of cognitive, social, and olfactory deficits, improves neural circuit function and enhances the clearance of soluble Aβ within hours in an apolipoprotein E-dependent manner [185, 186].…”
Section: Evidence That Eofad Mutations and Endocrine Dyscrasia Inducementioning
confidence: 99%